SYNTHESIS OF GADOLINIUM GRAPHITIC-CARBON NITRIDE (Gd/g-C₃N₄) COMPOSITE FOR THEIR BIOLOGICAL APPLICATIONS (Journal of Medical & Health Sciences Review, 2025)
In this study, we reported on the possibility of the new material gadolinium-doped carbon nitride (Gd/g-C₃N₄) composite and last documented checks for its antimicrobial properties, antioxidant, and biocompatibility. The Gd/g-C₃N₄ composite was prepared and evaluated for biotoxicity and antioxidant activity, bacterial biofilm inhibition in “Escherichia coli” and “Staphylococcus aureus”. Cytotoxicity profiles were further analyzed with the help of hemolysis assay and as per the results obtained, Gd/g-C₃N₄ exerted mild eryptosis, 10.05% while g-C₃N₄-DMF, 4.78%. The anti-radical activities were predicted using DPPH assay; g-C₃N₄-DMF showed a higher percentage radical scavenging ability of 48.09 % than Gd/g-C₃N₄ of 36.27 %. For antibacterial testing, the potential to inhibit the “E. coli” and “S. aureus” bio movie formation was analyzed, and it could be seen that the developed Gd/g-C₃N₄ significantly performed slightly better compared to the g-C₃N₄-DMF. These results show that the Gd/g-C₃N₄ composite possesses relatively satisfactory biological properties, but the biocompatibility and the antibacterial performance of the material should be enhanced when applied to disinfection and antifouling coatings.